Debating Arab Authoritarianism - K. Luisa Gandolfo (International Institute of Islamic Thought, 2009)
The Middle East has long contended with the title of the region most lacking in democratic state structures, and while several countries endeavor to enforce a form of democracy, yet others preserve the frameworks that efficiently sustain their monarchies, revenue, and power status in the area. The twin questions of how and why democracy has proved elusive in theMiddle East forms the crux of the collection of essays comprised within Schlumberger’s tome: Debating Arab Authoritarianism: Dynamics and Durability in Nondemocratic Regimes. Spanning Morocco to Oman, via Egypt, Jordan, and Saudi Arabia, the authoritarian mode of governance is surveyed through an assessment of the durability of regimes, the role of Islamist political parties, intra-regime dynamics, and the economic aspects of political reform. Divided into four sections, the book’s structure incorporates key elements of Arab authoritarianism: “State-Society Relations and Political Opposition,” “The Regimes,” “The Economy and the Polity,” and “The InternationalArena.” That the sections retain a subtle reluctance to address the link between the repressive capacities ofArab states and their longevity, as well as the concept that Islam is incompatible with democracy, is conspicuous, yet prudent. Far from retreadingworn theories, the contributors provide fresh conceptual and comparative analyses of individual countries and the region on a wider level, in addition to prospects for the respective regimes ...